Global ecological politics - Leonard, Liam; Barry, John, 1966- (Advances in ecopolitics, 2010)
"Advances in Ecopolitics Series" presents a collection of environmental alternatives worthy of consideration in light of the ongoing economic downturn which has accompanied the latest incarnation of unsustainable practices. Each publication discusses a significant element in the environmental theory which now represents an important aspect of sustainable living. The latest volume, "Global Ecological Politics", examines the range of environmental campaigns that are occurring across the planet. It showcases a selection of case studies on grassroots initiatives and activism in areas such as green economic alternatives, regional activism in defence of communities, alternative or utopian communities, green politics and ecotourism. This extensive array of ecological participation demonstrates that viable green alternatives are available in this current era of legitimation crisis across the formal political and economic sectors. "Global Ecological Politics" presents an important collection of articles for researchers, lecturers and academics in the socio-economic and political sector and is essential reading for those involved in all areas of environmentalism.